(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Transformations in vernacular dwellings are often understood primarily as changes in physical form, while the cultural structures that sustain them receive far less scholarly attention. In Aceh, the traditional stilted Rumoh Aceh has been extensively replaced by the masonry Rumoh Batee, yet both continue to accommodate the same ritual practices across the life cycle—birth, marriage, growth and development, and death. This study argues that the persistence of these practices reveals a continuous cultural logic that structures domestic space beyond its formal and material transformation. Using an interpretive-structural approach grounded in Salura’s form–function–meaning framework, this research analyzes how ritual activities are spatialized in both house types. Fieldwork was conducted in two mukim, encompassing four cases of Rumoh Aceh and four of Rumoh Batee. The findings indicate that a single cultural value, Peumulia (to honor and dignify others), operates as an overarching spatial ordering principle. This value is expressed architecturally through the adaptive public conversion of domestic space during rituals, the hierarchical orientation of principal rooms, and respectful spatial segregation within kinship relations. The study contributes to an understanding of how cultural continuity can endure through architectural transformation, demonstrating that a change in physical form does not necessarily signify a change in cultural meaning.